Geospatial Analysis, Source Apportionment, and Ecological–Health Risks Assessment of Topsoil Heavy Metal(loid)s in a Typical Agricultural Area - Denghui Wei; Shiming Yang; Haidong Li; Ming Luo; Ying Wang; Yangshuang Wang; Yunhui Zhang; Bin Wang (Agriculture)
Soil environmental protection has become a pressing issue for sustainable development. This study collected 153 topsoil samples from a typical agricultural area to evaluate the contamination characteristics of heavy metal(loid)s (HMs), identify their potential sources, and assess the associated ecological and human health risks. The results showed that the mean concentration of HMs was in the order of Zn > Cr > Ni > Pb > Cu > As > Cd > Hg; all HMs were below their background levels, except Cd. The geo-accumulation index (Igeo) and improved Nemerow index (INI) revealed that the overall pollution level was considered as no or slight contamination, while HMs posed low ecological risk according to the ecological hazard factor (Ei) and potential ecological risk index (PERI). In addition, three main sources were identified through the positive matrix factorization (PMF) model: natural source (48.2%; contributed As, Ni, Cu, Pb, and Zn), coal burning and waste disposal (24%; contributed Hg and Cd), and agricultural activities (27.8%; contributed Cr). The human health risk (HHR) assessment model and Monte Carlo simulation were applied to evaluate human health risks, and the results suggested that children faced higher health risks than adults, with 45.83% of samples exceeding the non-carcinogenic acceptable limit. As and Cr were the main contributors to non-carcinogenic and carcinogenic risks, respectively. The findings contributed to the local environmental management and sustainable development of agriculture.